Piety, Politics, and Post-Islamism: Dhikr Akbar in Indonesia - Noorhaidi Hasan (Al-Jami'ah Research Centre, 2012)
Dhikr akbar has developed into a performance that provides the opportunity for the sharing of political ideas, thus helping to constitute and negotiate a new public sphere. It is one of the most remarkable developments in the public visibility of Islam in post-Suharto Indonesia. Involving reflexive actions which are significant in the construction of personal and social identity, the dhikr akbar has the ability to silently invoke relations, actions, symbols, meanings and codes, and also to bind in one symbolic package changing roles, statues, social structures and ethical and legal rules. An active religiosity which takes the form of peaceful, esoteric expressions, the dhikr akbar represents a new sense of piety. To some extent, it can be conceptualized as an alternative to religious fundamentalism, an outward-oriented activism tempted to change the society or existing system with one based on religion. Normally performed in a cultural space which attracts public esteem, it serves as a concentrated moment of communality and expression of a community’s faith and, at the same time, a means of empowering political, social and economic networks.[Dhikr Akbar berkembang menjadi ‘panggung’ di mana gagasan politik dapat disemai, karena itu berperan dalam mengokohkan dan menegosiasi ruang publik baru. Dhikr Akbar adalah salah satu bentuk ritual Islam di ruang publik yang berkembang pasca Orde Baru. Melalui aktifitas reflektif yang berperan dalam pembentukan identitas personal dan sosial, dhikr akbar mampu memunculkan relasi, aksi, simbol, makna, dan kode, sekaligus untuk mempertemukan kesemuanya dalam satu bentuk simbol peran yang berubah, status, struktur sosial, dan etika serta aturan hukum. Sebagai satu bentuk religiusitas aktif yang berbentuk corak Islam yang tenang dan berorientasi pada dimensi dalam-esoteris, dhikr akbar dapat disebut pula sebagai satu bentuk kesalehan baru. Bentuk kesalehan dapat juga merupakan bentuk keagamaan yang berbeda dengan fundamentalisme, yang berorientasi pada aktifisme dimensi luar dengan tujuan merubah masyarakat atau sistem yang berlaku dengan sistem yang dianggap Islami. Dhikr akbar yang biasanya diselenggarakan di ruang budaya menarik perhatian masyarakat. Kegiatan ini menjadi aktifitas yang mampu menyatukan komunalitas dan ekspresi agama serta pada saat yang sama, mempertemukan jaringan politik, sosial, dan ekonomi.